2013
DOI: 10.1111/acfi.12048
|View full text |Cite
|
Sign up to set email alerts
|

Interactive data and retail investor decision-making: an experimental study

Abstract: The results of an experimental study of retail investors' use of eXtensible Business Reporting Language tagged (interactive) data and PDF format for making investment decisions are reported. The main finding is that data format made no difference to participants' ability to locate and integrate information from statement footnotes to improve investment decisions. Interactive data were perceived by participants as quick and 'accurate', but it failed to facilitate the identification of the adjustment needed to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Janvrin et al 2013report that nonprofessional investors provided with IDV spend less time doing tasks than when using non-IDV. Other research confirms this and notes that non-professional investors perform quicker financial statement analyses using IDV (Locke, Lowe, & Lymer, 2015).…”
Section: The Effect Of Idv and Task Characteristics On Decision Procesupporting
confidence: 64%
“…Janvrin et al 2013report that nonprofessional investors provided with IDV spend less time doing tasks than when using non-IDV. Other research confirms this and notes that non-professional investors perform quicker financial statement analyses using IDV (Locke, Lowe, & Lymer, 2015).…”
Section: The Effect Of Idv and Task Characteristics On Decision Procesupporting
confidence: 64%
“…Lambert et al (2019) do not find a significant change in forecast accuracy post-XBRL but instead highlight more frequent analyst forecast announcements. Regarding possible causes of missing improvements, Locke et al (2015) observe that different accounting methods employed by companies make ratios generated automatically by the software incomparable. Chowdhuri et al (2014) verify this semantic heterogeneity as a fundamental issue of XBRL interoperability.…”
Section: Cluster "Decision Making / Market Efficiency / Corporate Governance"mentioning
confidence: 99%
“…An example of a concern in this context is that automated analysis may compare numbers of apparently the same accounting concepts but whose measurement and importance vary with the circumstances of the entity (Locke et al, 2015;Valentinetti and Rea, 2012). Similarly, an interviewee observed that: … if there are two exact same things and there is no tag for it … it's not comparable by a computer so that is an issue.…”
Section: User Conversionmentioning
confidence: 99%